A method of electrolytically separating an aluminium-plastic composite
Patent Information
- Application Number
- CN202611270325.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-20
- Publication Date
- 2026-10-16
AI Technical Summary
[0006]依据本申请一个或多个实施例提供一种电解分离铝塑复合材料的方法,解决了传统铝塑材料分离工艺能耗高、分离效率低、塑料损失大、分离不彻底且不环保、安全风险高的技术问题
本申请的电解分离铝塑复合材料的方法,通过预处理使铝塑复合材料中的每个铝层至少部分暴露,再将暴露的铝层和阳极集流体形成多点电接触,从而得到阳极,以惰性电极作为阴极,将阳极、阴极置于容纳有电解液的电解槽中进行电解,铝层溶解为铝离子,从而实现和塑料层的分离,最终得到含铝离子的电解液和较完整的塑料层。该方法采用的电解液为包含NaCl和Na2SO4的水溶液,在特定电解条件(采用恒电位电解,电解的阳极工作电位为-0.8 V~-1.2 V)下,满足电解液导电性的同时,使阳极主要发生单质铝氧化为铝离子的反应,阴极主要生成氢气,而避免生成其他影响安全性或污染环境的副反应,例如产生氧气或氯气。恒电位电解可以是直流恒电位电解或脉冲恒电位电解,电解的阳极电流密度为50 A/m2~300 A/m2可避免铝层局部过热熔化或塑料层热损伤,从而保持最终分离得到的塑料层的完整性。此外,通过使暴露的铝层和所述阳极集流体形成多点电接触可促进铝层各部位溶解速率均匀,从而降低局部过溶解或溶解不彻底的问题,提高分离的质量,降低塑料层铝残留量。
Smart Images

Figure CN122913201A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of solid waste resource utilization technology, and in particular to a method for electrolytic separation of aluminum-plastic composite materials. Background Technology
[0002] Aluminum-plastic composite materials (such as Tetra Pak, pharmaceutical blister packs, and lithium battery aluminum-plastic films) are made by bonding an extremely thin aluminum layer (6μm~40μm) with a plastic layer (PE, PP, PET, PVC, nylon, etc.) using adhesives. They are widely used in the food, pharmaceutical, and electronics industries. Due to the tight bond between the aluminum and plastic layers, and their low aluminum content and thin thickness, these materials have long been considered difficult-to-recycle waste, relying heavily on landfill or incineration for disposal, resulting in serious resource waste and environmental pollution.
[0003] Traditional separation technologies for aluminum-plastic composites mainly include high-temperature melting, mechanical-physical separation, chemical dissolution, organic solvent methods, and electrochemical methods. High-temperature melting involves heating the aluminum-plastic composite to above 660℃, melting the aluminum layer and separating it from the plastic. This method is extremely energy-intensive, and the plastic component is completely incinerated, resulting in not only the loss of plastic resources but also the generation of toxic gases such as dioxins, causing severe environmental pollution. Mechanical-physical separation utilizes gravity differences or electrostatic effects after crushing and grinding. This method is incomplete, with residual aluminum fragments in the plastic severely affecting the quality of recycled plastics, resulting in low aluminum recovery rates, and the grinding process is energy-intensive. Chemical dissolution uses acid or alkali solutions to dissolve the aluminum layer for separation. This method severely corrodes the plastic matrix (especially PET and nylon), leading to a significant decrease in the mechanical properties of the recycled plastic; furthermore, using alkali solutions to dissolve the aluminum layer generates hydrogen gas with the entrainment of large amounts of alkali mist, resulting in high purification costs and difficulty in precisely controlling the hydrogen production rate. While acid dissolution is fast, acid mist and equipment corrosion are also significant problems. The organic solvent method separates aluminum from plastic by dissolving the plastic layer with organic solvents. This method suffers from difficulties in solvent recovery, significant volatile organic compound (VOC) pollution and safety risks, and high solvent costs. The electrochemical method treats aluminum-based materials using electrochemical principles. This method typically requires an electrochemical system containing chloride ion electrolytes, which carries the safety hazard of chlorine evolution as a side reaction.
[0004] In summary, traditional processes generally suffer from drawbacks such as high energy consumption, low efficiency, significant plastic loss, incomplete separation, heavy pollution, and high safety risks.
[0005] Therefore, there is an urgent need to develop a new separation method that is highly efficient, can simultaneously and completely recover aluminum and plastic, and is safe and pollution-free. Summary of the Invention
[0006] According to one or more embodiments of this application, a method for electrolytic separation of aluminum-plastic composite materials is provided, which solves the technical problems of high energy consumption, low separation efficiency, large plastic loss, incomplete separation, environmental unfriendliness, and high safety risks in traditional aluminum-plastic material separation processes.
[0007] This application provides a method for electrolytically separating aluminum-plastic composite materials, comprising the following steps: pre-treating the aluminum-plastic composite material containing at least one aluminum layer and at least one plastic layer to expose at least partially the aluminum layer, obtaining a pre-treated material; the pre-treatment includes one or more of crushing, surface grinding, and sandblasting; fixing the pre-treated material to an anode current collector, so that the exposed aluminum layer and the anode current collector are in contact, obtaining an anode; and using an inert electrode as a cathode, placing the anode and the cathode in an electrolytic cell containing an electrolyte for electrolysis, obtaining an electrolyte containing aluminum ions and the plastic layer; wherein the electrolyte contains NaCl, Na2SO4, and water, the electrolysis is DC constant potential electrolysis or pulse constant potential electrolysis, the electrolysis temperature is 15 ℃~40 ℃, and the anode current density of the electrolysis is 50 A / m. 2 ~300 A / m 2 The working potential of the anode in the electrolysis is -0.8 V to -1.2 V.
[0008] Optionally, the total salt concentration in the electrolyte is 0.5 mol / L to 2.5 mol / L, and the molar ratio of NaCl to Na2SO4 is (1~10):1.
[0009] Optionally, the electrolyte further contains a complexing agent with a molar concentration of 0.05 mol / L to 0.2 mol / L, and the pH of the electrolyte is 3 to 7.
[0010] Optionally, the complexing agent includes one or more of citric acid, EDTA, tartaric acid, and sulfosalicylic acid.
[0011] Optionally, the cathode is a platinum electrode, a nickel electrode, a graphite electrode, a stainless steel electrode, or a titanium-based coated electrode.
[0012] Optionally, the anode current collector has a mesh structure or a plate structure, and the pretreatment material and the anode current collector achieve multi-point electrical contact through compression.
[0013] Optionally, the electrolysis is pulsed constant potential electrolysis, wherein the pulsed constant potential electrolysis uses a square wave, the frequency of the pulsed constant potential electrolysis is 10 Hz to 50 Hz, the duty cycle of the pulsed constant potential electrolysis is 40% to 60%, the anode high potential of the pulsed constant potential electrolysis is -1.2V to -1.1V, the anode low potential of the pulsed constant potential electrolysis is -0.8V to -0.7V, the ratio of the anode high current density to the anode low current density of the pulsed constant potential electrolysis is (2~3):1, and the anode high current density of the pulsed constant potential electrolysis is 300 A / m. 2 ~350 A / m 2 The low current density of the anode in the pulsed constant potential electrolysis is 100 A / m. 2 ~150 A / m 2 .
[0014] Optionally, the electrolyte enters the electrolytic cell at a flow rate of 0.1 m / s to 0.5 m / s.
[0015] Optionally, the electrolyte flows upward from the bottom of the electrolytic cell.
[0016] Optionally, the electrolysis process monitors the cell voltage change in real time, the cell voltage is 0.4V~1.4V, and the anode current is cut off when the cell voltage increases by 30% or more; and / or, the electrolysis process monitors the aluminum ion concentration in the electrolyte in real time, and adjusts the anode average current density and electrolysis time according to the real-time value of the aluminum ion concentration in the electrolyte.
[0017] Optionally, the preprocessing may further include thickness grading.
[0018] Optionally, the pretreated material has a quadrilateral cross-section with a side length of 2cm to 5cm.
[0019] Optionally, the pretreatment step further includes performing thickness grading on the pretreatment material with a quadrilateral cross-section according to its thickness to obtain a first-level pretreatment material with a thickness of 6μm~10μm, a second-level pretreatment material with a thickness of 10μm~25μm, and a third-level pretreatment material with a thickness of 25μm~40μm.
[0020] Optionally, the first-stage pretreatment material uses 30 A / m 2 ~120 A / m 2 The electrolysis is performed using an anolyte current density of 120 A / m³, and the electrolysis time is 1-2 hours. 2 ~200 A / m 2The electrolysis is performed at an anolyte current density of d, and the electrolysis time is 2h~3.5h; the third-stage pretreatment material uses 200 A / m 2 ~300 A / m 2 The electrolysis is performed at an anode current density for a duration of 3.5 h to 5 h.
[0021] Optionally, the method further includes adjusting the pH of the aluminum-containing electrolyte to generate aluminum hydroxide precipitate or electrolyzing the aluminum-containing electrolyte to prepare metallic aluminum; and / or, the method further includes recycling and granulating the separated plastic layer; and / or, the method further includes collecting the hydrogen gas generated at the cathode during the electrolysis process.
[0022] Compared with the prior art, the technical solution provided in this application has the following beneficial effects: The method for electrolytic separation of aluminum-plastic composite materials disclosed in this application involves pretreatment to expose at least partially each aluminum layer in the composite material. The exposed aluminum layers are then brought into multi-point electrical contact with an anode current collector to form the anode. An inert electrode is used as the cathode. The anode and cathode are placed in an electrolytic cell containing an electrolyte for electrolysis. The aluminum layers dissolve into aluminum ions, thus separating them from the plastic layer. The final product is an electrolyte containing aluminum ions and a relatively intact plastic layer. The electrolyte used in this method is an aqueous solution containing NaCl and Na₂SO₄. Under specific electrolysis conditions (potential electrolysis with an anode working potential of -0.8 V to -1.2 V), the electrolyte conductivity is satisfied while ensuring that the anode primarily undergoes the oxidation of elemental aluminum to aluminum ions, and the cathode primarily generates hydrogen gas. This avoids the generation of other side reactions that could affect safety or pollute the environment, such as the production of oxygen or chlorine gas. The potential electrolysis can be direct current potential electrolysis or pulsed potential electrolysis, with an anode current density of 50 A / m. 2 ~300 A / m 2 This avoids localized overheating and melting of the aluminum layer or thermal damage to the plastic layer, thus maintaining the integrity of the final separated plastic layer. Furthermore, by creating multi-point electrical contact between the exposed aluminum layer and the anode current collector, a uniform dissolution rate is promoted across the aluminum layer, reducing the problem of localized over-dissolution or incomplete dissolution, improving separation quality, and reducing the amount of aluminum residue in the plastic layer.
[0023] The electrolytic separation method for aluminum-plastic composite materials disclosed in this application can be carried out at a relatively low temperature (15 ℃~40 ℃), without the need for additional heating throughout the process. The energy consumption is low, only 1 / 30 to 1 / 50 of that of the high-temperature melting method, and there are no toxic gases such as dioxins produced by plastic incineration. The reaction is rapid.
[0024] The electrolytic separation method for aluminum-plastic composites disclosed in this application dissolves aluminum in the aluminum layer under electrochemical driving. The aluminum dissolution rate under room-temperature electrochemical driving is much higher than that under room-temperature chemical etching. This method reduces the processing time by more than 80% compared to the room-temperature alkaline dissolution method. For typical aluminum-plastic composites, the processing time is only 0.5 to 5 hours, and no heating is required throughout the process, avoiding thermal aging of the plastic. It should be noted that because aluminum undergoes a self-corrosion hydrogen evolution reaction (chemical dissolution) in a chloride-containing electrolyte, some aluminum dissolves directly without passing through the electrochemical circuit. Therefore, the aluminum dissolution efficiency of this method can reach over 95%, while the anolyte current efficiency is typically between 15% and 30%. This phenomenon does not affect the separation effect or the total amount of hydrogen produced; on the contrary, it is a favorable factor for the rapid dissolution of aluminum.
[0025] The electrolytic separation method for aluminum-plastic composite materials disclosed in this application thoroughly separates the aluminum and plastic layers, achieves a high aluminum removal rate without damaging the plastic matrix, maintains the integrity and reuse value of the plastic, and retains ≥85% of the mechanical properties of the plastic.
[0026] The electrolytic separation method for aluminum-plastic composite materials disclosed in this application offers flexible aluminum recovery methods with high purity. Aluminum enters the solution in an ionic state, facilitating the preparation of high-purity aluminum compounds or metallic aluminum through precipitation or electrolysis. The aluminum dissolution efficiency can reach over 95%.
[0027] The method for electrolytic separation of aluminum-plastic composite materials disclosed in this application is environmentally friendly, clean, and the electrolyte can be recycled with a cycle count of ≥50 times. It produces no high-temperature incineration waste gas, generates little waste liquid, and is simple to treat. The overall process is green and environmentally friendly.
[0028] The electrolytic separation method for aluminum-plastic composite materials disclosed in this application is precise and controllable. By adjusting parameters such as anode current density and electrolysis time, the degree of aluminum layer dissolution can be precisely controlled, avoiding excessive dissolution and damage to the plastic matrix, resulting in a high yield.
[0029] The electrolytic separation method for aluminum-plastic composite materials disclosed in this application releases no harmful gases such as chlorine, ensuring production safety and compliance with emission standards for exhaust gases. The chlorine concentration in the exhaust gas can be lower than the detection limit (0.1 ppm), making it safe and environmentally friendly.
[0030] The electrolytic separation method for aluminum-plastic composite materials disclosed in this application produces low-energy-consumption green hydrogen as a byproduct, meeting green energy requirements. The hydrogen produced at the cathode can be collected, purified, and used as a clean energy source, significantly improving energy utilization efficiency. Processing 1 ton of aluminum-plastic composite material (15% aluminum content) can produce approximately 16.7 kg of hydrogen, valued at approximately 334-501 yuan, while simultaneously reducing CO2 emissions by approximately 120 kg.
[0031] The electrolytic separation method for aluminum-plastic composite materials of this application can also be adapted to materials of different thicknesses. Through technical solutions such as thickness grading pretreatment, it can adapt to aluminum-plastic composite materials with different aluminum layer thicknesses in the range of 6μm~40μm, ensuring the consistency of the treatment effect and expanding the scope of application of the process. Attached Figure Description
[0032] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this application and disclosure, and together with the description serve to explain the principles of this application and disclosure.
[0033] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0034] Figure 1 This is a schematic flowchart of a method for electrolytically separating aluminum-plastic composite materials according to some embodiments of this application. Detailed Implementation
[0035] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0036] In this application, except where expressly stated, any matters or issues not mentioned are directly applicable to those known in the art without any modification. Furthermore, any implementation described in this application can be freely combined with one or more other implementations described in this application, and the resulting technical solutions or concepts shall be considered part of the original disclosure or original record of this application, and should not be regarded as new content not disclosed or anticipated in this application, unless those skilled in the art consider the combination to be clearly unreasonable.
[0037] Any method steps, processes, and operations described in this application should not be construed as necessarily requiring them to be performed in a particular order as discussed or shown, unless explicitly specified. It should also be understood that additional or alternative steps may be used unless otherwise stated.
[0038] In this application, the technical features described in an open-ended manner include both closed technical solutions consisting of the listed features and open technical solutions that include the listed features.
[0039] Any specific numerical values disclosed herein (including the endpoints of numerical ranges) are not limited to their exact values, but should be understood to also include values close to the exact value, such as all possible values within ±5% of the exact value. Furthermore, with respect to the disclosed numerical ranges, one or more new numerical ranges can be obtained by arbitrarily combining the endpoint values of the range, the endpoint values with specific point values within the range, and the specific point values themselves; these new numerical ranges should also be considered as specifically disclosed herein.
[0040] Unless otherwise stated, the terms used herein have the same meaning as commonly understood by those skilled in the art, and if a term is defined herein and its definition differs from the common understanding in the art, the definition herein shall prevail.
[0041] Please see Figure 1 This application provides a method for electrolytically separating aluminum-plastic composite materials, comprising the following steps: S1, pre-treating an aluminum-plastic composite material containing at least one aluminum layer and at least one plastic layer to expose at least part of the aluminum layer, to obtain a pre-treated material, wherein the pre-treatment includes one or more of crushing treatment, surface grinding treatment and sandblasting treatment; S2, the pretreated material is fixed to the anode current collector, so that the exposed aluminum layer and the anode current collector come into contact, thus obtaining the anode; and S3, using an inert electrode as the cathode, the anode and cathode are placed in an electrolytic cell containing an electrolyte for electrolysis to obtain an electrolyte containing aluminum ions and a plastic layer.
[0042] In step S3 above, the electrolyte contains NaCl, Na2SO4, and water. The electrolysis is performed using a constant potential electrolysis method, which can be either direct current constant potential electrolysis or pulsed constant potential electrolysis. The electrolysis temperature is 15 ℃~40 ℃, and the anolyte current density is 50 A / m³. 2 ~300 A / m 2 The anolyte working potential of the above electrolysis is -0.8 V to -1.2 V, and this anolyte working potential is measured using a saturated calomel electrode as a reference electrode.
[0043] The method for electrolytic separation of aluminum-plastic composite materials provided in the above embodiments of this application involves pretreatment to expose at least partially each aluminum layer in the aluminum-plastic composite material, followed by multi-point electrical contact between the exposed aluminum layers and the anode current collector to obtain the anode. An inert electrode is used as the cathode, and the anode and cathode are placed in an electrolytic cell containing an electrolyte for electrolysis. The aluminum layers dissolve into aluminum ions, thereby achieving separation from the plastic layer, ultimately yielding an electrolyte containing aluminum ions and a relatively intact plastic layer. The electrolyte used in this method is an aqueous solution containing NaCl and Na2SO4. Under specific electrolysis conditions (constant potential electrolysis, with the anode working potential at -0.8 V to -1.2 V), while ensuring the conductivity of the electrolyte, the anode primarily undergoes the oxidation of elemental aluminum to aluminum ions, while the cathode primarily generates hydrogen gas, avoiding the generation of other side reactions that affect safety or pollute the environment, such as the production of oxygen or chlorine gas. The constant potential electrolysis can be direct current constant potential electrolysis or pulsed constant potential electrolysis, with an anode current density of 50 A / m. 2 ~300 A / m 2 This avoids localized overheating and melting of the aluminum layer or thermal damage to the plastic layer, thus maintaining the integrity of the final separated plastic layer. Furthermore, by creating multi-point electrical contact between the exposed aluminum layer and the anode current collector, the dissolution rate of the aluminum layer is promoted to be uniform across its various parts, thereby reducing the problem of localized over-dissolution or incomplete dissolution and improving the quality of the separation.
[0044] It should be noted that the aluminum-plastic composite material of this application refers to a multi-layer structure formed by bonding a layer of metallic aluminum or its alloy foil / plate with a thermoplastic polymer layer through an adhesive layer. Since the adhesive forms a very thin coating in the aluminum-plastic composite material, its thickness is negligible, and the adhesive remains attached to the thermoplastic polymer layer after electrolytic separation, the adhesive layer and the thermoplastic polymer layer can be considered as a single unit. The plastic layer includes a thermoplastic polymer matrix layer and a thermosetting adhesive layer. The materials of the thermoplastic polymer matrix layer include, but are not limited to, polyolefins (polyethylene PE, polypropylene PP), polyesters (polyethylene terephthalate PET), polyamides (nylon PA), polyvinyl chloride (PVC), and combinations thereof. The materials of the thermosetting adhesive layer include, but are not limited to, polyurethane adhesives, acrylic adhesives, epoxy resin adhesives, and combinations thereof.
[0045] The aluminum-plastic composite material comprises at least one aluminum layer (aluminum conductive layer) and at least one plastic layer (insulating layer). The aluminum layer serves as the anode conductor during the electrolysis process, and the plastic layer serves as the insulating matrix. The aluminum and plastic layers are alternately stacked. The composite process includes any one of dry lamination, extrusion lamination, or hot-pressing lamination. The aluminum layer is selected from industrially pure aluminum or aluminum alloys, which contain aluminum and other impurity elements (such as iron, silicon, etc.), wherein the total mass content of the impurity elements is ≤ 1.5%; preferably, the aluminum content of the aluminum layer is ≥ 99.0%. Exemplarily, the aluminum layer is one of grades 8011, 8021, and 8079. The thickness of the aluminum layer is preferably 6μm to 40μm, but is not limited thereto.
[0046] As a typical structure of this application, the aluminum-plastic composite material is a symmetrical structure consisting of a plastic layer A (comprising a thermoplastic polymer matrix layer A and an adhesive layer), an aluminum layer, and a plastic layer B (comprising a thermoplastic polymer matrix layer B and an adhesive layer) stacked sequentially, wherein the aluminum layer is completely covered by the plastic layer. To facilitate electrolyte penetration and anolyte current conduction, the aluminum layer is at least partially exposed through the pretreatment in step S1, for example, at least one side or end face (i.e., the cut surface) is exposed to the outside and not covered by the plastic layer. During electrolysis, the electrolyte penetrates through this exposed aluminum layer. The aluminum layer acts as the anode, and its electrons are discharged through the external circuit, causing aluminum atoms to lose electrons and transform into Al³⁺. + Ions are removed, while the insulating plastic and adhesive layers remain intact due to their non-conductivity, thus achieving selective delamination between the layers. In some specific embodiments, the aluminum-plastic composite material is first subjected to a crushing process (e.g., shearing, shredding, grinding, etc.) to generate numerous torn edges and curled structures, thereby exposing the edges of the aluminum layer to the outside, resulting in fragmented material. The fragmented material is then subjected to surface grinding or sandblasting to selectively remove localized plastic layers, forming multiple discrete conductive contact points on the surface of the aluminum layer, which then serve as pretreatment material. Exemplarily, the crushing process can be performed using a high-speed disc shredder. In other embodiments, the aluminum-plastic composite material further comprises a paper layer. To separate the paper layer, a hydraulic pulping pretreatment can be performed using a hydraulic pulper. Through the mechanical action of the pulper rotor, the paper layer fibers are dissociated and dispersed in water to form a pulp suspension. This suspension is then filtered through a pressure screen or inclined screen to separate the pulp fibers from the solid aluminum-plastic composite layer.
[0047] In some embodiments, the pretreatment material has a quadrilateral cross-section with a side length of 2cm to 5cm.
[0048] The inventors of this application have also discovered a correlation between current density and the thickness of the pretreatment material during electrolysis. When the thickness of the pretreatment material increases, the current density needs to be increased or the electrolysis time extended to ensure complete dissolution of the aluminum. Conversely, when the thickness of the pretreatment material decreases, the current density needs to be decreased or the electrolysis time shortened. If the current density is too low, the center of the aluminum layer is difficult to penetrate; if the current density is too high, it can easily cause anodic polarization overheating, which may lead to localized overheating and melting of the aluminum layer or thermal damage to the plastic layer.
[0049] In some embodiments, the pretreatment step further includes thickness grading of the pretreatment material with a quadrilateral cross-section according to its thickness, resulting in a first-level pretreatment material with a thickness of 6 μm to 10 μm, a second-level pretreatment material with a thickness of 10 μm to 25 μm, and a third-level pretreatment material with a thickness of 25 μm to 40 μm. The thickness grading method can employ online detection using an eddy current thickness gauge or pre-classify according to the material source type.
[0050] In some implementations, the first-stage pretreatment material uses 30 A / m 2 ~120 A / m 2 Electrolysis is performed using an anolyte current density of 120 A / m for 1-2 hours; the second-stage pretreatment material uses 120 A / m 2 ~200 A / m 2 Electrolysis is performed using an anolyte current density of 200 A / m³ for a duration of 2 to 3.5 hours; the third-stage pretreatment material uses a current density of 200 A / m³. 2 ~300 A / m 2 The electrolysis is performed using an anolyte current density for a duration of 3.5 to 5 hours. It should be noted that, after thickness grading, pretreated materials of different thicknesses can be processed in separate electrolytic cells to ensure complete electrolysis of each batch of material without over-electrolysis.
[0051] In some embodiments, in step S2, the anode current collector contacts multiple torn edges, grinding exposure points, and curling protrusions exposed in the aluminum layer. These torn edges, grinding exposure points, and curling protrusions all serve as conductive contact points, forming multi-point electrical contact with the anode current collector. In some embodiments, the anode current collector employs a mesh or plate structure, preferably a titanium mesh or stainless steel mesh. The pretreatment material forms a three-dimensional conductive network with the anode current collector, resulting in lower contact resistance. In some embodiments, in step S2, the pretreatment material is fixed to the anode current collector by compression, which further improves the stability of the multi-point electrical contact. Exemplarily, the pretreatment material can be fixed to the anode current collector by mechanical compression or conductive clamps.
[0052] The cathode is an inert electrode, which can be selected from corrosion-resistant conductive materials. In some embodiments, the cathode is a platinum electrode, a nickel electrode, a graphite electrode, a stainless steel electrode, or a titanium-based coated electrode. A titanium-based coated electrode refers to a composite electrode in which a layer of noble metal oxide (such as RuO2, IrO2, or Ta2O5) is coated onto the surface of a titanium metal substrate (such as a titanium plate or titanium mesh) through methods such as thermal decomposition or electrodeposition. It should be noted that the titanium mesh current collector described in this application is a titanium metal mesh without noble metal oxide coating (i.e., bare titanium), whose surface only has a naturally passivated titanium dioxide (TiO2) layer, unlike the titanium-based coated electrode. The titanium-based coated electrode is more conducive to hydrogen evolution as a cathode. Furthermore, a gas diffusion structure can be provided on the cathode surface to facilitate hydrogen escape.
[0053] In some embodiments, the total salt concentration in the electrolyte is 0.5 mol / L to 2.5 mol / L, and the molar ratio of NaCl to Na₂SO₄ is (1~10):1. Exemplarily, the total salt concentration in the electrolyte is 0.5 mol / L, 1.0 mol / L, 1.5 mol / L, 2.0 mol / L, or 2.5 mol / L. Exemplarily, the molar ratio of NaCl to Na₂SO₄ is 1:1, 2:1, 3:1, 3.5:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, or 10:1. In an electrolyte system containing NaCl and Na₂SO₄, a total salt concentration of 0.5 mol / L to 2.5 mol / L and a molar ratio of NaCl to Na₂SO₄ of (3.5~10):1 can ensure higher conductivity of the electrolyte while suppressing the chlorine evolution side reaction.
[0054] In some embodiments, the electrolyte also contains a complexing agent with a molar concentration of 0.05 mol / L to 0.20 mol / L, and the pH of the electrolyte is 3 to 7. The complexing agent can form a complex with aluminum ions, preventing the direct formation of aluminum hydroxide precipitate on the anode surface and hindering further aluminum dissolution. Simultaneously, the complexation between the complexing agent and aluminum ions can also suppress the chlorine evolution side reaction. The electrolyte pH is maintained at neutral or weakly acidic. Under neutral conditions (pH 6.5 to 7.5), the main anode reaction is Al → Al. 3+ +3e The main reaction at the cathode is 2H₂O + 2e⁻. → H2↑ + 2OH Under weakly acidic conditions (pH 3-6.5), the main anodic reaction is Al → Al. 3+ + 3e The main reaction at the cathode is 2H. + + 2e → H2↑. Since the complexing agent has a certain influence on the pH value of the electrolyte, the complexing effect of the complexing agent is more favorable when the molar concentration of the complexing agent is 0.05 mol / L~0.2 mol / L and the pH of the electrolyte is 3~7, while avoiding the reaction with Al after the pH of the electrolyte changes.
[0055] For example, the molar concentration of the complexing agent is 0.05 mol / L, 0.06 mol / L, 0.08 mol / L, 0.10 mol / L, 0.12 mol / L, 0.14 mol / L, 0.16 mol / L, 0.18 mol / L, or 0.20 mol / L.
[0056] For example, the pH of the electrolyte is 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5 or 7.
[0057] For example, the complexing agent includes, but is not limited to, one or more of citric acid, EDTA, tartaric acid, and sulfosalicylic acid. The inventors of this application have also discovered that the complexing agent is related to the thickness of the pretreatment material during electrolysis. Citric acid is preferably used as the complexing agent for the first-stage pretreatment material with a thickness of 6 μm to 10 μm, EDTA is preferably used as the complexing agent for the second-stage pretreatment material with a thickness of 10 μm to 25 μm, and sulfosalicylic acid is preferably used as the complexing agent for the third-stage pretreatment material with a thickness of 25 μm to 40 μm.
[0058] It should be noted that the electrolyte in this application can be recycled after replenishment and adjustment.
[0059] For example, the electrolysis temperature is 15°C, 20°C, 25°C, 30°C, 35°C, or 40°C. Within this electrolysis temperature range, the electrolysis process does not require external heating and can be carried out at room temperature.
[0060] It should be noted that the electrolysis in this application can be either DC constant potential electrolysis or pulsed constant potential electrolysis. When electrolysis is DC constant potential electrolysis, the anode current density refers to the initial apparent current density, i.e., the total current divided by the effective projected area of the anode current collector. During electrolysis, the anode potential is applied at any value between -0.8 V and -1.2 V to prevent side reactions such as chlorine evolution. As electrolysis proceeds, the initial apparent current density gradually decreases due to the gradual thinning of the aluminum layer and the reduction of the effective anode area. When electrolysis is pulsed constant potential electrolysis, the anode potential alternates between -0.8 V (high anode potential) and -1.2 V (low anode potential) in a pulsed manner, and the anode current strictly follows: at the high anode potential, the current rises to the high anode current density; at the low anode potential, the current drops to the low anode current density. The anode current density in pulsed constant potential electrolysis refers to the average current density. At the same anolyte current density (the anolyte current density in pulsed potentiostatic electrolysis is the average current density), the effective interface temperature under pulsed potentiostatic electrolysis is much lower than that under DC potentiostatic electrolysis, which is more conducive to avoiding local overheating and melting of the aluminum layer or thermal damage to the plastic layer. If the anolyte current density is too low, the aluminum layer dissolution rate is too slow, resulting in poor economic efficiency, and prolonged electrolysis leads to an increase in the proportion of chemical self-corrosion; if the anolyte current density is too high, it will lead to overheating of anolyte polarization, causing local overheating and melting of the aluminum layer or thermal damage to the plastic layer. For example, the anolyte current density of electrolysis is 50 A / m. 2 100 A / m 2 150A / m 2 200A / m 2 250A / m 2 Or 300A / m 2 .
[0061] It should be further noted that the anodic operating potential of -0.8 V to -1.2 V is a relative value measured relative to a saturated calomel electrode (SCE). If other reference electrodes (such as Ag / AgCl) are used, the value should be calculated according to the formula. A conversion is performed to make the actual electrode potential of the working electrode equivalent to that of this application. For example, the anode working potential is -0.8 V, -0.9 V, -1.0 V, -1.1 V, or -1.2 V.
[0062] In some embodiments, electrolysis is pulsed constant-potential electrolysis. The pulse waveform of pulsed constant-potential electrolysis is a square wave with a frequency of 10 Hz to 50 Hz and a duty cycle of 40% to 60%. The anode high potential is -1.2V to -1.1V, the anode low potential is -0.8V to -0.7V, and the ratio of the anode high current density to the anode low current density is (2~3):1. Optionally, the anode high current density of pulsed constant-potential electrolysis is 300 A / m. 2 ~350 A / m 2The low current density of the anode in pulsed constant potential electrolysis is 100 A / m. 2 ~150 A / m 2 This pulsed constant potential electrolysis can significantly reduce the concentration polarization overpotential at the anode interface, refine the dissolution process, and improve the uniformity of aluminum dissolution, making it particularly suitable for aluminum-plastic composites with thicker aluminum layers.
[0063] For example, the frequency of pulsed potentiostatic electrolysis is 10 Hz, 20 Hz, 30 Hz, 40 Hz or 50 Hz.
[0064] For example, the duty cycle of pulsed potentiostatic electrolysis is 40%, 45%, 50%, 55% or 60%.
[0065] For example, the anode has a high current density of 300 A / m 2 310 A / m 2 320 A / m 2 330 A / m 2 340 A / m 2 Or 350 A / m 2 .
[0066] For example, the anode low current density is 100 A / m 2 110 A / m 2 120 A / m 2 130 A / m 2 140 A / m 2 Or 150 A / m 2 .
[0067] To further eliminate overpotential caused by concentration polarization, in some embodiments, the electrolyte enters the electrolytic cell at a flow rate of 0.1 m / s to 0.5 m / s. For example, the electrolyte is transported using a circulating pump, and the flow rate can be 0.1 m / s, 0.2 m / s, 0.3 m / s, 0.4 m / s, or 0.5 m / s.
[0068] In some implementations, the electrolyte flows upward from the bottom of the electrolytic cell, creating an upward liquid flow support force to prevent the plastic layer from collapsing.
[0069] In some implementations, a porous pressure plate is placed above the pretreated material to restrict its upward deformation.
[0070] In some embodiments, the cell voltage change is monitored in real time during the electrolysis process, and the current density can be reduced when the cell voltage increases (anodic effect). In some specific embodiments, the cell voltage is 0.4V~1.4V, and the anode current is cut off when the cell voltage increases by 30% or more.
[0071] In some implementations, the concentration of aluminum ions in the electrolyte is monitored in real time during the electrolysis process, and the average current density of the anode and the electrolysis time are adjusted according to the real-time value of the aluminum ion concentration in the electrolyte.
[0072] In some embodiments, the method further includes pausing electrolysis every 30 to 50 minutes, taking samples to detect the amount of aluminum residue, and adjusting subsequent electrolysis parameters based on the amount of aluminum residue to ensure that pretreated materials of different thicknesses all achieve the target dissolution rate.
[0073] In some embodiments, a multi-stage series electrolytic cell is employed, with the anode current density of the multi-stage series electrolytic cell decreasing progressively. For example, it may include a first-stage electrolytic cell, a second-stage electrolytic cell, and a third-stage electrolytic cell connected in series. The anode current density of the first-stage electrolytic cell is greater than that of the second-stage electrolytic cell, and the anode current density of the second-stage electrolytic cell is greater than that of the third-stage electrolytic cell. The pretreatment material passes through each stage of the electrolytic cell sequentially. The higher anode current density in the preceding stage of the electrolytic cell allows for rapid dissolution of most of the aluminum, while the lower current density in the subsequent stage of the electrolytic cell precisely dissolves any remaining aluminum and avoids damage to the plastic layer. The residence time of the pretreatment material in each stage of the electrolytic cell can be automatically adjusted according to the thickness.
[0074] In some embodiments, the method further includes adjusting the pH of the aluminum-containing electrolyte to generate aluminum hydroxide precipitate or electrolyzing the aluminum-containing electrolyte to prepare metallic aluminum. In some embodiments, the aluminum-containing electrolyte can also be used directly as an aluminum-containing liquid product.
[0075] In some embodiments, the method further includes recycling and granulating the separated plastic layer. In still other embodiments, the separated plastic layer is washed with a polar organic solvent (such as ethyl acetate), selectively swollen and peeled off the adhesive layer to obtain a thermoplastic polymer matrix layer, which is then granulated.
[0076] In some embodiments, the method further includes collecting the hydrogen gas generated at the cathode during electrolysis. In some specific embodiments, the electrolytic cell adopts a closed design with a gas collection hood at the top to collect the hydrogen gas generated at the cathode, which is then washed with water, dried with molecular sieves, and metered. The exhaust gas is treated by a dilute NaOH absorption tower before being discharged.
[0077] Example To better understand this application, the following description, in conjunction with embodiments, further illustrates this application. However, the scope of protection claimed in this application is not limited to the scope of the embodiments.
[0078] In the following embodiments, unless otherwise specified, all experimental instruments and raw material components and quantities involved are commercially available products or can be prepared by known methods. Experimental methods not specifying specific conditions in the embodiments were performed under conventional conditions, such as those described in literature, books, or methods recommended by the manufacturer. Unless otherwise specified, the specific parameters used in each step of the material preparation process in each embodiment and comparative example are the same.
[0079] The test methods or test conditions for aluminum dissolution efficiency and plastic recovery rate in the following embodiments and comparative examples are as follows: First, three representative samples were randomly selected, and the aluminum content (m1), adhesive content (m2), and plastic content (m3) in the samples were determined by EDS or chemical dissolution method.
[0080] Based on this, the aluminum layer content in this batch of aluminum-plastic composite waste can be obtained:
[0081] in, This represents the mass ratio of the aluminum layer components in the sample.
[0082] Similarly, the plastic layer content in this batch of aluminum-plastic composite waste can be obtained:
[0083] in, This represents the mass ratio of the plastic layer in the sample.
[0084] After electrolysis, 5 mL of homogeneous electrolyte was taken, and 0.5 mL of analytical grade nitric acid (68%) was added. The mixture was then digested on a hot plate at 80 °C for 15 min. After cooling, the solution was filtered through a 0.45 μm needle filter, and the filtrate was diluted to 100 mL with ultrapure water. The mass concentration of aluminum was determined using ICP-OES (inductively coupled plasma optical emission spectrometry) at a wavelength of 396.152 nm for Al. .
[0085] Aluminum dissolution efficiency is calculated using the following formula:
[0086] in, The total volume of the electrolyte (L) This represents the total weight of the aluminum-plastic composite material in this batch. Each test condition was repeated three times, and the average value was taken to ensure data reliability.
[0087] After electrolysis, the obtained plastic skeleton is cleaned to remove residual electrolyte and dried to remove moisture. The treated waste is then weighed to obtain the weight m of the remaining material. 余 .
[0088] Plastic recycling rate is calculated using the following formula:
[0089] ( () is used to represent the recycled plastic skeleton minus any undissolved aluminum layer.
[0090] Example 1: Separation of Thin Aluminum Layer Food Packaging Waste food aluminum-plastic packaging film (aluminum layer thickness approximately 6μm, plastic layer PET / PE composite, aluminum layer located between PET and PE) was collected, washed, and cut into approximately 3cm × 3cm fragments with naturally curled edges. Eddy current thickness gauge analysis showed a thickness of 6μm, classifying it as a first-level pre-treatment material.
[0091] The first-stage pretreatment material was uniformly spread onto the titanium mesh anode current collector and pressed together with a clamping frame to form multi-point electrical contacts, serving as the anode. A graphite plate was used as the cathode, and a saturated calomel electrode as the reference electrode. The electrolyte was an aqueous solution containing NaCl, Na₂SO₄, and citric acid, with a NaCl molar concentration of 1.0 mol / L, a Na₂SO₄ molar concentration of 0.5 mol / L, and a citric acid molar concentration of 0.08 mol / L. The electrolyte pH was 4.5, the electrode spacing between the cathode and anode was 5 cm, the electrolysis temperature was 25℃, and the electrolyte flow rate was 0.2 m / s. A DC constant potential electrolysis mode was adopted, controlling the anode operating potential at -1.0 V (vs. SCE), corresponding to an initial anode current density of 100 A / m. 2 Electrolysis lasts for 1.5 hours. The electrolytic cell is a closed design with a gas collection hood at the top to collect the hydrogen gas generated at the cathode. The hydrogen gas is then washed with water, dried with molecular sieves, and metered.
[0092] Test results: After electrolysis, the PET / PE composite plastic layer was completely retained, the plastic recovery rate was 95.5%, the aluminum residue was 0.38% (EDS test), and the tensile strength retention rate was 91.3%. The aluminum dissolution efficiency was 96.2% (ICP-OES test), the aluminum ion concentration in the electrolyte reached 8.7 g / L, and the anolyte current efficiency was 17.2%. The hydrogen yield was 92.5%, approximately 10.2 L of hydrogen was collected (standard conditions), the hydrogen purity was 99.2%, and the unit hydrogen power consumption was 3.2 kWh / Nm³. 3 The chlorine concentration in the exhaust gas was below the detection limit (0.1 ppm), and no chlorine was released. The cell voltage remained stable at 0.8V~0.9V during the electrolysis process.
[0093] It should be noted that the low anodic current efficiency detected in this embodiment is due to the self-corrosion and hydrogen evolution of aluminum in the chloride-containing electrolyte. The actual aluminum dissolution rate is much higher than the pure electrochemical dissolution rate, so the separation efficiency is not affected. In addition, the trace amount of hydrogen generated by self-corrosion is collected, which helps to improve the hydrogen yield.
[0094] Example 2: Tetra Pak aluminum-plastic separation Waste Tetra Pak cartons were collected and the paper layers were pre-separated using a hydraulic pulper to obtain an aluminum-plastic composite layer (the aluminum layer is approximately 7 μm thick, and the plastic layer is PE). After cleaning and drying, the aluminum-plastic layer was cut into approximately 3cm x 3cm fragments, and the surface of the fragments was lightly sandblasted to expose multiple points of the aluminum layer. Eddy current thickness gauge measurements showed a thickness of 7 μm, classifying it as a first-stage pre-treated material.
[0095] The first-stage pretreatment material was evenly spread onto the titanium mesh anode current collector and pressed firmly with a clamping frame to create multi-point contact between the aluminum layer of the first-stage pretreatment material and the titanium mesh, serving as the anode. A graphite plate was used as the cathode, and a saturated calomel electrode as the reference electrode. The electrolyte was an aqueous solution containing NaCl, Na₂SO₄, and citric acid, with a NaCl molar concentration of 1.2 mol / L, a Na₂SO₄ molar concentration of 0.4 mol / L, and a citric acid molar concentration of 0.10 mol / L. The electrolyte pH was 5, the electrode spacing between the cathode and anode was 5 cm, the electrolysis temperature was 25℃, and the electrolyte flow rate was 0.2 m / s. A DC constant potential electrolysis mode was adopted, controlling the anode operating potential at -0.9 V (vs. SCE), corresponding to an initial anode current density of approximately 150 A / m. 2 Electrolysis lasts for 2 hours. The electrolytic cell is a closed design with a gas collection hood at the top to collect the hydrogen gas generated at the cathode. The hydrogen gas is then washed with water, dried with molecular sieves, and metered.
[0096] Test Results: After electrolysis, the plastic layer was removed, washed, dried, and weighed. The plastic recovery rate was 96.2%, and the aluminum residue was 0.32% (EDS test). The PE layer was intact without significant damage, and the tensile strength retention rate was 92.5%. The aluminum ion concentration in the electrolyte reached 12.3 g / L (ICP-OES test), with an aluminum dissolution efficiency of 96.8% and a current efficiency of 18.7%. The hydrogen yield was 93.8%, with approximately 14.5 L of hydrogen collected (standard conditions). The hydrogen purity was 99.3%, and the unit hydrogen power consumption was 3.0 kWh / Nm³. 3 The chlorine concentration in the exhaust gas was below the detection limit (0.1 ppm), and no chlorine was released. The cell voltage remained stable between 0.85V and 0.95V during the electrolysis process.
[0097] It should be noted that the low anodic current efficiency detected in this embodiment is due to the self-corrosion and hydrogen evolution of aluminum in the chloride-containing electrolyte. The actual aluminum dissolution rate is much higher than the pure electrochemical dissolution rate, so the separation efficiency is not affected. In addition, the trace amount of hydrogen generated by self-corrosion is collected, which helps to improve the hydrogen yield.
[0098] Example 3: Separation of pharmaceutical blister packaging Waste aluminum-plastic blister packaging material (aluminum layer thickness approximately 20μm, plastic layer PVC) was collected, washed, and then broken into approximately 2cm fragments. The fragments were irregularly curled with the aluminum layer peeling off at the edges. Eddy current thickness gauge readings showed a thickness of 20μm, classifying it as a second-stage pre-treatment material.
[0099] The second-stage pretreatment material was stacked on a stainless steel anode plate and pressed together with conductive clamps to form multi-point electrical contact, serving as the anode. A titanium-based RuO2 coated electrode was used as the cathode, and a saturated calomel electrode as the reference electrode. The electrolyte was an aqueous solution containing NaCl, Na2SO4, and EDTA, with a NaCl molar concentration of 1.5 mol / L, a Na2SO4 molar concentration of 0.5 mol / L, and an EDTA molar concentration of 0.12 mol / L. The electrolyte pH was 6, the electrode spacing between the anode and cathode was 5 cm, the electrolysis temperature was 30℃, and the electrolyte flow rate was 0.3 m / s. A DC constant potential electrolysis mode was adopted, controlling the anode operating potential at -1.0 V (vs. SCE), corresponding to an initial anode current density of 200 A / m², and electrolysis for 3.5 h. The electrolytic cell adopted a closed design, with a gas collection hood at the top to collect the hydrogen gas generated at the cathode, which was then washed with water, dried with molecular sieves, and metered.
[0100] Test results: After electrolysis, the PVC plastic layer remained intact and could be directly crushed and granulated after washing and drying. The plastic recovery rate was 95.8%, the aluminum residue was 0.41% (EDS detection), and the tensile strength retention rate was 90.2%. The aluminum ion concentration in the electrolyte reached 28.5 g / L (ICP-OES detection), the aluminum dissolution efficiency was 97.2%, and the current efficiency was 21.3%. The hydrogen yield was 94.2%, with approximately 33.6 L of hydrogen collected (standard conditions), a hydrogen purity of 99.1%, and a unit hydrogen power consumption of 2.8 kWh / Nm³. The chlorine concentration in the tail gas was below the detection limit (0.1 ppm), and no chlorine was released. The cell voltage remained stable between 0.9 V and 1.0 V during the electrolysis process.
[0101] It should be noted that the anolyte current efficiency in this embodiment is relatively low because aluminum undergoes self-corrosion and hydrogen evolution in the chloride-containing electrolyte. The actual aluminum dissolution rate is much higher than the pure electrochemical dissolution rate, and the separation efficiency is not affected.
[0102] Example 4: Separation of Aluminum-Plastic Film from Lithium-ion Batteries Waste lithium battery aluminum-plastic film (approximately 40 μm thick aluminum layer, outer nylon, inner CPP layer) was taken and cut into 5cm x 5cm fragments. Due to the relatively thick aluminum layer, the edges of the fragments were lightly polished to expose multiple points on the aluminum layer cross-section. Eddy current thickness gauge readings showed a thickness of 40 μm, classifying it as a third-level pretreatment material.
[0103] The third-stage pretreatment material was fixed onto a titanium mesh anode to form multi-point electrical contacts, serving as the anode. A graphite plate was used as the cathode, and a saturated calomel electrode as the reference electrode. The electrolyte was an aqueous solution containing NaCl, Na₂SO₄, and sulfosalicylic acid, with the following molar concentrations: NaCl 0.8 mol / L, Na₂SO₄ 0.3 mol / L, and sulfosalicylic acid 0.05 mol / L. The electrolyte pH was 4, the electrode spacing between the anode and cathode was 5 cm, the electrolysis temperature was 35℃, and the electrolyte flow rate was 0.4 m / s. A pulsed constant potential electrolysis method was employed with the following parameters: frequency 25 Hz, duty cycle 50%, square wave, anode high potential -0.8 V, anode low potential -1.2 V (vs. SCE), corresponding to anode high current density and anode low current density of 300 A / m². 2 and 100 A / m 2 The total electrolysis time is 4 hours. The electrolytic cell adopts a closed design with a gas collection hood at the top to collect the hydrogen gas generated at the cathode. After being washed with water and dried with molecular sieves, the hydrogen gas is metered.
[0104] Test results: After electrolysis, both the nylon outer layer and the CPP inner layer remained intact, with no obvious corrosion or swelling. The plastic layer was completely recyclable, with a plastic recovery rate of 97.1%. The aluminum residue was 0.28% (EDS test), and the tensile strength retention rate was 93.8%. The aluminum dissolution efficiency was 98.5% (ICP-OES test), with an aluminum ion concentration of 42.6 g / L in the electrolyte and a current efficiency of 24.5%. The hydrogen yield was 95.6%, with approximately 50.2 L of hydrogen collected (standard conditions). The hydrogen purity was 99.4%, and the unit hydrogen power consumption was 2.6 kWh / Nm³. 3 The chlorine concentration in the exhaust gas was below the detection limit (0.1 ppm), and no chlorine was released. The average cell voltage during the electrolysis process was approximately 1.0 V.
[0105] It should be noted that the anolyte current efficiency in this embodiment is relatively low because aluminum undergoes self-corrosion and hydrogen evolution in the chloride-containing electrolyte. The actual aluminum dissolution rate is much higher than the pure electrochemical dissolution rate, and the separation efficiency is not affected.
[0106] Example 5: Grading treatment of mixed thickness materials Mixed aluminum-plastic waste (including thin-layered aluminum food packaging, Tetra Pak cartons, pharmaceutical blister packs, and lithium battery aluminum-plastic films, with aluminum layer thicknesses ranging from 6 to 40 μm) was collected and classified online using an eddy current thickness gauge before being processed separately. Aluminum-plastic waste with a thickness of 6 μm to 10 μm was classified as the first-stage pretreatment material and processed according to the conditions of Example 1; aluminum-plastic waste with a thickness of 10 μm to 25 μm was classified as the second-stage pretreatment material and processed according to the conditions of Example 3; and aluminum-plastic waste with a thickness of 25 to 40 μm was classified as the third-stage pretreatment material and processed according to the conditions of Example 4. Constant potential control and an adaptive power-off mechanism were used at the endpoint for each stage.
[0107] Test results: All pretreatment materials at each stage achieved good separation results. The first-stage pretreatment material achieved an aluminum dissolution efficiency of 96.0% and a plastic recovery rate of 95.3%; the second-stage pretreatment material achieved an aluminum dissolution efficiency of 97.0% and a plastic recovery rate of 95.6%; the third-stage pretreatment material achieved an aluminum dissolution efficiency of 98.3% and a plastic recovery rate of 96.8%. The overall aluminum dissolution efficiency was 97.2%, the overall plastic recovery rate was 95.9%, and the overall mechanical property retention rate was 91.5%. The chlorine concentration in the exhaust gas at each stage was below the detection limit (0.1 ppm). The overall unit hydrogen power consumption was 2.9 kWh / Nm³. 3 Compared to the thickest third-stage pretreatment material, the tiered treatment reduces the electrolysis time of the first-stage pretreatment material by 60%, lowers energy consumption by 45%, and avoids plastic damage caused by over-electrolysis of the thinner pretreatment material.
[0108] Comparative Example 1: Room Temperature Alkali Dissolution Method Take the same Tetra Pak aluminum-plastic composite layer fragments as in Example 2, place them in a 1 mol / L NaOH solution with a liquid-to-solid ratio of 20 mL: 1 g, react at 25 °C, and stir slowly for 12 h. After the reaction, observe that most of the aluminum layer has dissolved, but the PE plastic layer shows obvious swelling, whitening, and thinning in some areas.
[0109] Test results: Aluminum dissolution efficiency was 88.6%, plastic recovery rate was 90.2%, aluminum residue was 1.8% (EDS test), and plastic tensile strength retention rate was only 48.5%. Hydrogen gas contained alkaline mist during the reaction; after water washing, hydrogen purity was approximately 96.2%. The processing time was as long as 12 hours, and the mechanical properties of the plastic were severely damaged.
[0110] Comparative Example 2: No complexing agent Take the same Tetra Pak aluminum-plastic composite layer fragments as in Example 2, and use the same electrolysis conditions as in Example 2, but without adding citric acid complexing agent to the electrolyte.
[0111] Test results: After 2 hours of electrolysis, the aluminum dissolution efficiency was 72.3%, a large amount of white Al(OH)3 precipitate adhered to the surface of the plastic skeleton, the aluminum residue was 3.8% (EDS detection), and the plastic recovery rate was 92.1%. Because the Al(OH)3 precipitate covered the aluminum layer surface, it hindered further aluminum dissolution, significantly reducing the dissolution efficiency.
[0112] Comparative Example 3: Single-point electrical contact Take the same Tetra Pak aluminum-plastic composite layer fragments as in Example 2, and use the same electrolysis conditions as in Example 2, but only form a single point electrical contact at the center of the fragment with conductive tape, instead of forming a multi-point electrical contact network.
[0113] Test results: After 2 hours of electrolysis, the aluminum dissolution efficiency was 68.5%, and the aluminum residue in some areas of the plastic layer was as high as 8.2% (EDS test). The uneven dissolution was obvious. The aluminum was completely dissolved in the area near the electrical contact point, while the aluminum layer in the area far from the electrical contact point was almost undissolved.
[0114] Comparative Example 4: Current density exceeds range Take the same Tetra Pak aluminum-plastic composite layer fragments as in Example 2, and use the same electrolysis conditions as in Example 2, but with an anolyte current density of 600 A / m. 2 .
[0115] Test results: After 1 hour of electrolysis, the aluminum dissolution efficiency was 85.2%, but the plastic PE layer showed obvious thermal deformation and local melting, with a tensile strength retention rate of only 72.5%. Due to excessively high current density, the aluminum layer overheated locally, leading to thermal damage to the plastic layer.
[0116] Comparative Example 5: Ungraded Mixed Treatment Take the same mixed aluminum-plastic waste as in Example 5, without grading, and directly apply it under the conditions of Example 4 (300 A / m). 2 , 4h) unified processing.
[0117] Test results: The aluminum dissolution efficiency of aluminum-plastic waste with a thickness of 25-40 μm was 97.8%. However, due to excessive electrolysis, the plastic layer of aluminum-plastic waste with a thickness of 6 μm-10 μm showed significant corrosion, and the tensile strength retention rate was only 78.3%. Furthermore, the energy consumption of aluminum-plastic waste with a thickness of 6 μm-10 μm was severely wasted. The overall retention rate of plastic mechanical properties was 82.5%, lower than the 91.5% of the graded treatment.
[0118] Comparative Example 6: High Concentration NaCl without Potentiostatic Control Take the same Tetra Pak aluminum-plastic composite layer fragments as in Example 2, and use a 4 mol / L high-concentration NaCl electrolyte. Electrolyze in constant current mode without constant potential control, with an anolyte current density of 150 A / m. 2 Electrolysis was performed for 2 hours. After electrolysis, power was applied for another 30 minutes to simulate the electrolysis scenario.
[0119] Test results: The aluminum dissolution efficiency during the normal electrolysis stage was 95.8%, which is close to that of Example 2. However, after 30 minutes of electrolysis, a chlorine concentration of 3.2 ppm was detected in the exhaust gas, exceeding the limit of 0.5 ppm in the "Integrated Emission Standard for Air Pollutants", indicating a risk of chlorine release.
[0120] The above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of this application.
[0121] Although preferred embodiments have been described in this specification, those skilled in the art, upon learning the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments as well as all changes and modifications falling within the scope of this specification.
[0122] Obviously, those skilled in the art can make various modifications and variations to this specification without departing from its spirit and scope. Therefore, if such modifications and variations fall within the scope of the claims and their equivalents, this specification is also intended to include such modifications and variations.
Claims
1. A method for electrolytically separating aluminum-plastic composite materials, characterized in that, Includes the following steps: An aluminum-plastic composite material comprising at least one aluminum layer and at least one plastic layer is pretreated to expose at least part of the aluminum layer to obtain a pretreated material. The pretreatment includes one or more of crushing, surface grinding and sandblasting. The pretreated material is fixed to the anode current collector, so that the exposed aluminum layer and the anode current collector come into contact to obtain the anode; as well as Using an inert electrode as the cathode, the anode and the cathode are placed in an electrolytic cell containing an electrolyte for electrolysis to obtain an electrolyte containing aluminum ions and a plastic layer. The electrolyte comprises NaCl, Na₂SO₄, and water; the electrolysis is either DC constant potential electrolysis or pulsed constant potential electrolysis; the electrolysis temperature is 15℃~40℃; and the anolyte current density is 50 A / m³. 2 ~300 A / m 2 The working potential of the anode in the electrolysis is -0.8 V to -1.2 V.
2. The method according to claim 1, characterized in that, The total salt concentration in the electrolyte is 0.5 mol / L to 2.5 mol / L, and the molar ratio of NaCl to Na2SO4 is (1~10):
1.
3. The method according to claim 1, characterized in that, The electrolyte also contains a complexing agent with a molar concentration of 0.05 mol / L to 0.2 mol / L, and the pH value of the electrolyte is 3 to 7.
4. The method according to claim 3, characterized in that, The complexing agent includes one or more of citric acid, EDTA, tartaric acid, and sulfosalicylic acid.
5. The method according to claim 1, characterized in that, The cathode is a platinum electrode, nickel electrode, graphite electrode, stainless steel electrode, or titanium-based coated electrode.
6. The method according to any one of claims 1 to 5, characterized in that, The anode current collector has a mesh structure or a plate structure, and the pretreatment material and the anode current collector achieve multi-point electrical contact through compression.
7. The method according to any one of claims 1 to 5, characterized in that, The electrolysis is pulsed constant potential electrolysis, which uses a square wave. The frequency of the pulsed constant potential electrolysis is 10 Hz to 50 Hz, the duty cycle is 40% to 60%, the anode high potential is -1.2V to -1.1V, the anode low potential is -0.8V to -0.7V, the ratio of the anode high current density to the anode low current density is (2~3):1, and the anode high current density is 300A / m. 2 ~350 A / m 2 The low current density of the anode in the pulsed constant potential electrolysis is 100 A / m. 2 ~150 A / m 2 .
8. The method according to any one of claims 1 to 5, characterized in that, The electrolyte enters the electrolytic cell at a flow rate of 0.1 m / s to 0.5 m / s.
9. The method according to claim 8, characterized in that, The electrolyte flows upward from the bottom of the electrolytic cell.
10. The method according to any one of claims 1 to 5, characterized in that, The electrolysis process monitors the cell voltage change in real time. The cell voltage is between 0.4V and 1.4V. When the cell voltage increases by 30% or more, the anode current is cut off; and / or, The concentration of aluminum ions in the electrolyte is monitored in real time during the electrolysis process, and the anode current density and electrolysis time are adjusted according to the real-time value of the aluminum ion concentration in the electrolyte.
11. The method according to any one of claims 1 to 5, characterized in that, The preprocessing also includes thickness grading.
12. The method according to claim 11, characterized in that, The pretreated material has a quadrilateral cross-section with a side length of 2cm to 5cm.
13. The method according to claim 12, characterized in that, The pretreatment step further includes performing thickness grading on the pretreatment material with a quadrilateral cross-section according to its thickness to obtain a first-level pretreatment material with a thickness of 6μm~10μm, a second-level pretreatment material with a thickness of 10μm~25μm, and a third-level pretreatment material with a thickness of 25μm~40μm.
14. The method according to claim 13, characterized in that, The first-stage pretreatment material uses 30 A / m 2 ~120A / m 2 The electrolysis is performed at an anolyte current density for a duration of 1 to 2 hours. The second-stage pretreatment material uses 120 A / m 2 ~200 A / m 2 The electrolysis is performed at an anolyte current density for a duration of 2 to 3.5 hours. The third-stage pretreatment material uses 200 A / m 2 ~300 A / m 2 The electrolysis is performed at an anode current density for a duration of 3.5 h to 5 h.
15. The method according to claim 1, characterized in that, It also includes, by adjusting the pH of the aluminum-containing electrolyte to generate aluminum hydroxide precipitate, or by electrolyzing the aluminum-containing electrolyte to prepare metallic aluminum; and / or, It also includes recycling and granulating the separated plastic layer; And / or, It also includes collecting the hydrogen gas generated at the cathode during the electrolysis process.